2009
DOI: 10.1152/ajprenal.00086.2009
|View full text |Cite
|
Sign up to set email alerts
|

Histone deacetylase-2 is a key regulator of diabetes- and transforming growth factor-β1-induced renal injury

Abstract: Excessive accumulation of extracellular matrix (ECM) in the kidneys and epithelial-to-mesenchymal transition (EMT) of renal tubular epithelial cells contributes to the renal fibrosis that is associated with diabetic nephropathy. Histone deacetylase (HDAC) determines the acetylation status of histones and thereby controls the regulation of gene expression. This study examined the effect of HDAC inhibition on renal fibrosis induced by diabetes or transforming growth factor (TGF)-beta1 and determined the role of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
196
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 245 publications
(213 citation statements)
references
References 45 publications
14
196
0
Order By: Relevance
“…[40] HDAC 2 PLAYS IMPORTANT ROLE IN DN [10] Among the six HDACs tested (HDAC-1 through -5 and HDAC-8), HDAC-2 activity significantly amplified in the kidneys of STZ-induced diabetic rats and db/db mice and TGF-β1-treated NRK52-E cells.…”
Section: World Journal Of Pharmacy and Pharmaceutical Sciencesmentioning
confidence: 99%
See 3 more Smart Citations
“…[40] HDAC 2 PLAYS IMPORTANT ROLE IN DN [10] Among the six HDACs tested (HDAC-1 through -5 and HDAC-8), HDAC-2 activity significantly amplified in the kidneys of STZ-induced diabetic rats and db/db mice and TGF-β1-treated NRK52-E cells.…”
Section: World Journal Of Pharmacy and Pharmaceutical Sciencesmentioning
confidence: 99%
“…[13] Trichostatin A, a nonselective HDAC inhibitor, reduced mRNA and protein expressions of ECM modules and prevented EMT. [10] IV] CURCUMIN [18] Increased levels of HSP-27 and MAP kinase (p38) in diabetic kidney. However, curcumin treatment prevented this increase in HSP-27 and p38 expression.…”
Section: Omprakash World Journal Of Pharmacy and Pharmaceutical Sciementioning
confidence: 99%
See 2 more Smart Citations
“…In addition, PARP and NF-γB signaling was performed by p300 pathways in diabetic retina, kidney and heart, and led to extracellular matrix (ECM) components augmentation resulting in DVC (37)(38)(39)(40)(41)(42). Research in epigenetic showed that HDACs play a crucial role in TGF-β1-mediated ECM generation and renal parenchymal fibrosis (43)(44)(45). While, lysine acetylation is a temporary histone modification, it is presumably that histone methylation can be more constant and can play pivotal roles in diabetes vascular complications.…”
Section: Histone Modificationmentioning
confidence: 99%